Report on the promotion of the utilization of indigenous raw materials in the agro-industrial sector - Henry, Cadet ([CEDP] St. MichaelBB, 1992)
Looks at the present ability of the regional farm sector to produce for the processing sub-sector, and makes recommendations in regards to expansion of production of the farm sector in an attempt to satisfy the processing sector, where possible.